COVID-19 & UNESCO GLOBAL GEOPARK KALDERA TOBA: PELUANG DAN TANTANGAN PENGEMBANGAN PARIWISATA BERKELANJUTAN DI KAWASAN DANAU TOBA [COVID-19 & UNESCO GLOBAL GEOPARK TOBA CALDERA: OPPORTUNITIES AND CHALLENGES FOR SUSTAINABLE TOURISM DEVELOPMENT IN LAKE TOBA AREA] - Karmel Hebron Simatupang; Ignatius Ismanto (Universitas Pelita Harapan, 2021)
In the amidst of the Covid-19 pandemic, Toba Caldera was designated as a member of the UNESCO Global Geopark (UGG), in July 2020. This status becomes a very important opportunity and challenge in encouraging the development of sustainable tourism in the super-priority tourism destination of Lake Toba. This is following the demands of the new normal adaptation in the era of Covid-19. Thus, this paper aims to study and analyze how the status of Toba Caldera UGG amid the Covid-19 pandemic can be used as a strategy to strengthen the implementation of sustainable tourism development based on environmental, cultural and biological conservation. The research method was carried out with a descriptive qualitative approach, by conducting a literature study and interviews. In this study, it was found that the new normal of tourism in the Covid-19 pandemic era was in line with the spirit of conservation, restoration and revitalization of the Toba Caldera UGG geo-sites and thus strengthening the implementation of sustainable tourism in the Lake Toba region. In welcoming a better new normal era, the Government should not hesitate to take policies that prioritize environmental sustainability and discontinue the obsolete pattern of being greedy that harms the environment.Bahasa Indonesia Abstract: Di tengah pandemi Covid-19, Geopark Kaldera Toba ditetapkan menjadi anggota UNESCO Global Geopark (UGG), Juli 2020 yang lalu. Status ini menjadi peluang dan tantangan sangat penting dalam mendorong pengembangan pariwisata berkelanjutan di destinasi superprioritas Kawasan wisata Danau Toba. Hal ini bersesuaian dengan tuntutan adaptasi new normal dalam era pandemi Covid-19. Paper ini dengan demikian bertujuan untuk melakukan studi dan analisis bagaimana status UGG Kaldera Toba di tengah pandemi Covid-19 dapat menjadi siasat memperkuat implementasi pembangunan pariwisata berkelanjutan yang berbasis konservasi lingkungan, budaya dan hayati. Metode penelitian dilakukan dengan pendekatan kualitatif deskriptif, dengan melakukan studi literature dan wawancara. Dalam penelitian ini ditemukan bahwa new normal pariwisata era pandemi Covid-19 sejalan dengan semangat konservasi, restorasi dan revitalisasi situs-situs UGG Kaldera Toba dan dengan demikian dapat memperkuat implementasi pariwisata berkelanjutan di Kawasan Danau Toba. Dalam menyongsong era new normal yang lebih baik, agar Pemerintah tidak perlu ragu mengambil kebijakan yang mendahulukan kelestarian lingkungan dan menghentikan pola lama yang serakah pada lingkungan.